IDENTIFICATION OF X GENE MUTATIONS, GENOTYPE AND SUBGENOTYPE OF HEPATITIS B VIRUS (HBV) - Fatimawali .; Billy Kepel; Sitti Romlah; Catur Riany; Debbie Retnoningrum (Indonesian Journal of Pharmacy, 2014)
Infection of hepatitis B virus (HBV) is a global health problem, including in Indonesia. There are currently an estimated 2 billion people worldwide are infected with HBV, about 75% of them are in Asia and 350 million of them will develop into chronic hepatitis B. Factors that influence the development of chronic hepatitis B into liver carcinoma include x gene mutation, HBV genotype and subgenotype. This research aims to identify x gene mutation, genotype and subgenotype of HBV infecting hepatitis B patients in Manado associated with the onset of liver carcinoma. HBV DNAs were isolated from blood samples of 30 hepatitis B patients. X gen was amplified using nested PCR with pre-designed primer pairs. Amplified DNA fragments were electrophoresed in 1.5% agarose and visualized under UV. DNA fragments were then separated and purified using Qiagen column, then sequenced to determine their nucleotide sequences of x gene. Amino acid of x protein were deduced from nucleotide sequence of x gene and used as basic to determine HBV genotype and subgenotype. X protein was aligned with those similar protein with the same subgenotype retrieved from GenBank to determine if there was a mutation at amino acid.  The mutated x protein were compared with other mutation found in x protein in other literatures associated with the onset of liver carcinoma. Genotype and subgenotype of HBV isolated from blood samples of 10 patients was detected and showed that five patients were infected with B genotype HBV (2 patients were infected with B2 subgenotype, 2 patients with B3 subgenotype and 1 patient with B9 subgenotype). The rest of 5 patients were infected with C genotype HBV (1 patient with C1 subgenotype, 2 patients with C2 subgenotype,  and 2 patients with C5 subgenotype). The mutation in x protein is related significantly to the clinical severity of the liver and hepatocellular  carcinoma (HCC), ie V5L in subgenotype C2, and I127T and H94Y in subgenotype C5.